Student Perception Toward The Use of English as A medium of Instruction at The English Education Departement of Universitas Muhammadiyah Yogyakarta - Natalia Ariyani (PBI 15 UMY 066, 2015)
*66 This study aims to reveal the studentsâ€™ perception on the use of English as a medium of instruction at the English Education Department, Universitas Muhammadiyah Yogyakarta. This study underlined the background that the use of English by the students and the teacher is not optimal in teaching and learning process. Because of that, the students feel afraid to use English and prefer to use Indonesian language in the classroom. The researcher used qualitative research method in conducting this study. The data was obtained through interview. Participants were chosen by using snowballing sampling. There were six students Batch 2012 of EED UMY as the participants. After the data interview was transcribed and categorized, the researcher presented the result of this study in discussion. This study revealed that the students in fact thought that English as a medium of instruction is good to be implemented. Other than it, the students thought that the use of English by the students and the teachers needed to be improved. There were many students prefer to use Indonesian language in the classroom. Some teachers also often used Indonesian language to explain the material and to communicate with their students. Based on the result, students thought that EMI could help them get the language input. They also thought that EMI could improve their confidence and their English skills. However, it was also challenging for the students. They felt shy and afraid of making any mistakes when they used English in the classroom. Because of that, the students gave some suggestions about the use of English at EED UMY. This study also gave recommendation for the teacher to be consistent in using English as a medium of instruction in the classroom. The students should improve their awareness to use English, be active, and feel free to express their opinion the classroom. Then, it might be good if the institution implemented â€œEnglish Dayâ€ at EED UMY in order to improve the use of English by both students and teachers as much as possible.